Model Kepemimpinan Majelis Daerah Terhadap Tingkat Kepuasan Pendeta Gereja Pantekosta di Indonesia Provinsi Sulawesi Selatan - Rope, Denny (Jurnal Kala Nea, 2023)
The understanding of an organization as a structured system that has goals to be achieved together must be understood by all administrators and members. Including in Christian organizations so that they can achieve goals in accordance with the vision and mission of the organization. The Regional Assembly is a form of organizational leadership model owned by the Pentecostal Church in Indonesia. The chairman and members are elected and elected to carry out organizational tasks comprehensively. It poses a problem if the leadership of the regional assembly, which is a system where aspects of service, work commitment, communication and relational leadership and its members are not systematized. Leadership elements that emphasize service, work commitment, communication and relational aspects must be reflected in the field so as to cause success that correlates with one another. In this study the author found that the Regional Assembly Leadership Model as a church organization today has an impact on the satisfaction of pastors based on 1) service progress, 2) ability to solve problems, 3) achievement of work programs. To reveal and find answers to problems, facts and events that occur, in compiling and completing this research task using Quantitative methodology on 100 pastors as research objects.